PERAN KELUARGA DALAM MENANGGULANGI KENAKALAN REMAJA - Fauziah, Syarifah (PSW, 2015)
Adolescence is a period filled with changes and vulnerable to the emergence of problems (juvenile delinquency). For that we need special attention as well as a good understanding and proper handling of juveniles is an important factor for the success of young people in the next life, this is a time to remember the most decisive. Besides, it needs the cooperation of the teens themselves, parents, teachers and other parties concerned to adolescent development in education and other areas can be traversed in a focused, healthier and happier. To reduce conflicts of adolescent turmoil and to provide opportunities for teens to develop themselves optimally, need to be created nearby environmental conditions as stable as possible, especially the family environment. Family circumstances characterized by conjugal harmony will ensure teens get through the transition smoothly and undisturbed. As for some roles do parents in tackling juvenile kenkalan include; Parents should be exemplary attitude and speech on naknya, motivation of children, parents provide direction with whom and in communities where teens have to get along. Parents trying to create a harmonious family, communicative, and convenient for teens. and to help teenager good at choosing friends and a good environment for him